2015
DOI: 10.3324/haematol.2015.125864
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior treatment and depth of response on survival in MM-003, a randomized phase 3 study comparing pomalidomide plus low-dose dexamethasone versus high-dose dexamethasone in relapsed/refractory multiple myeloma

Abstract: Pomalidomide is a distinct oral IMiD® immunomodulatory agent with direct antimyeloma, stromalsupport inhibitory, and immunomodulatory effects. The pivotal, multicenter, open-label, randomized phase 3 trial MM-003 compared pomalidomide + low-dose dexamethasone vs high-dose dexamethasone in 455 patients with refractory or relapsed and refractory multiple myeloma after failure of bortezomib and lenalidomide treatment. Initial results demonstrated significantly longer progression-free survival and overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 27 publications
5
52
0
1
Order By: Relevance
“…Of note, achieving at least a minor response with Pom/Dex was found to have a major impact on outcome. Patients who achieved at least a 25% reduction of the M-spike had a median PFS of 7.4 months and a median overall survival of 17.2 months, versus 2.3 and 7.5 months for patients with less than a minor response [40]. This large Phase III trial confirmed the significant hematologic toxicity with grade 3-4 neutropenia occurring in 48% of patients.…”
Section: Clinical Efficacy In Phase I/ii Clinical Studiessupporting
confidence: 66%
See 1 more Smart Citation
“…Of note, achieving at least a minor response with Pom/Dex was found to have a major impact on outcome. Patients who achieved at least a 25% reduction of the M-spike had a median PFS of 7.4 months and a median overall survival of 17.2 months, versus 2.3 and 7.5 months for patients with less than a minor response [40]. This large Phase III trial confirmed the significant hematologic toxicity with grade 3-4 neutropenia occurring in 48% of patients.…”
Section: Clinical Efficacy In Phase I/ii Clinical Studiessupporting
confidence: 66%
“…Notably, the advantage in outcome was observed in very elderly patients (>75 years old), and in patients with high-risk cytogenetic features (17p deletion and t(4;14)) [39]. Moreover, the PFS benefit remained consistent regardless of prior therapies (i.e., lenalidomide as last prior therapy, number of prior therapies) [40]. Of note, achieving at least a minor response with Pom/Dex was found to have a major impact on outcome.…”
Section: Clinical Efficacy In Phase I/ii Clinical Studiesmentioning
confidence: 80%
“…The effect of Pom on the immune system coupled with the mechanism of action of ISA and preclinical data demonstrating significantly enhanced direct and indirect anti-MM cytotoxicity when ISA is combined with Pom [36] suggest that the combination of both drugs may improve the benefit seen with Pom/dex alone in clinical studies of patients with RRMM (median PFS: 4.0 months; median OS: 13.1 months) [45]. ISA has been investigated at three dose levels (5, 10 and 20 mg/kg) in combination with Pom/dex in a Phase Ib study of patients with RRMM (n = 26) treated with ≥2 previous lines of therapy and revealed promising results in terms of ORR and the safety profile [46].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that deeper responses are associated with better PFS if not overall survival. 141143 Therefore, it is our approach to try and achieve as deep a response as possible after the first relapse in an attempt to favorably affect overall survival, keeping in mind the presence of comorbidities, the quality of life of the patient, including the need for frequent and perhaps lengthy clinical visits, and the expense of therapy. Given the superiority of triple combination therapy for both newly diagnosed 144,145 and relapsed multiple myeloma, 29,33 we also generally prefer triple combination therapy for relapsed disease, as long as the patient can tolerate the therapy.…”
Section: Therapy For Patients In First Relapsementioning
confidence: 99%